W. H. Auden’s For The Time Being Christian proof? Aesthetic possibility? - Cappeluti, Jo-Anne (2016)
This article explores a noteworthy difference between Alan Jacobs’s interpretation of Auden’s oratorio and mine. Jacobs sees the oratorio as a Christian poem and proof of Auden’s Christianity—which coincides with Auden’s turn away from his Romantic roots. I interpret the piece as a sign of Auden’s continuing commitment to his Romantic inheritance and intent to serve as an aesthetic (not religious) hero, exploring the aesthetic possibilities to which his imagination is drawn. After delineating the problems each of us has in applying our respective claims, I explain mine as offering the more troublesome challenge of the two.